2002
DOI: 10.1046/j.1445-2197.2002.02523.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of patients with Borrmann type IV gastric carcinoma

Abstract: Improving the prognosis for patients with Borrmann type IV gastric carcinoma requires early detection and a curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 10 publications
5
42
1
Order By: Relevance
“…Like our study, several others confirmed that the B IV was associated with known factors of poor [5][6][7]11,14,16 . Diagnosis in advanced stages, poorly differentiated histology, serosal invasion and high incidence of lymph node involvement are factors that directly influence the prognosis, causing lower rates of curative operations, which can vary between 31 and 52% 3,[5][6][7][8]20 and are in agreement with our data, which was 42.3% (52/123). Some series have shown that up to 2/3 of these patients underwent non-curative operations 17,20 , which is why Aranha 10 states that linitis plastica is not a surgical disease.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Like our study, several others confirmed that the B IV was associated with known factors of poor [5][6][7]11,14,16 . Diagnosis in advanced stages, poorly differentiated histology, serosal invasion and high incidence of lymph node involvement are factors that directly influence the prognosis, causing lower rates of curative operations, which can vary between 31 and 52% 3,[5][6][7][8]20 and are in agreement with our data, which was 42.3% (52/123). Some series have shown that up to 2/3 of these patients underwent non-curative operations 17,20 , which is why Aranha 10 states that linitis plastica is not a surgical disease.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 88%
“…Despite advances in the treatment of gastric cancer, surgical results of B IV adenocarcinomas remain poor, the worst among all gastric carcinomas19. The survival rates at five years after curative gastrectomies rang from 11% to 33.4% 5,7,17,19 , confirming that they have lower rates compared to other Borrmann types 6,7,9 . In our patients, the overall survival at five years was 33%, similar to the ranges of variation found in the literature.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 70%
See 3 more Smart Citations